Principals’ Sensemaking of Coaching for Ambitious Reading Instruction in a High-Stakes Accountability Policy Environment - Matsumura, Lindsay Clare; Wang, Elaine (Education Policy Analysis Archives, 2014)
In the present exploratory qualitative study we examine the contextual factors that influenced the implementation of a multi-year comprehensive literacy-coaching program (Content-Focused Coaching, CFC). We argue that principals’ sensemaking of the dialogic instructional strategies promoted by the program in light of high-stakes accountability policies influenced coaches’ work with teachers. Principals’ views of the efficacy of the teaching strategies promoted by CFC for meeting accountability targets influenced how principals socially positioned coaches in schools (i.e., the degree to which they promoted coaches as sources of expertise to teachers), and the extent to which the coaching received by teachers focused on implementing dialogic teaching practices. Our results also suggest that principals’ sensemaking of the program was for the most part consistent across years, even in the face of shifting accountability status and changes in district leadership. Implications of our findings for improving the implementation of coaching programs are discussed.